Using Informal Articles in Extensive Reading (ER) Program: A Personal Experience - Chothibul Umam (Institut Agama Islam Negeri Imam Bonjol Padang, 2015)
In this digital age, informal articles which contain some valuable informations and extensive input to develop the learners’ language proficiency are easily found on internet or other reading sources. Unfortunately most literature shows that informal articles are not widely used in extensive reading (henceforth ER) program. For this reason, the paper introduces steps procedure in using informal articles as authentic material in one semester ER program for Indonesian EFL college learners. The procedure is developed on the basis of my great interest in creating innovative way in teaching ER at one of the State Institute for Islamic Studies in Indonesia. The proposed steps are expected to be an alternative pathway in teaching ER for English teachers particularly at a college-university level. Keywords: Extensive Reading, informal article.Copyright © 2015 by Al-Ta'lim All right reserved